Effect on changing of intake temperature to hydrogen-methane-diesel mixture combustion characteristics. Issue 1 (March 2020) - Sabah, Osama; Mohammad, Taib Iskandar; Abu Mansor, Mohd Radzi
Abstract: Ultra clean fuels generally used along with the conventional fuels such as Compressed Natural Gas (CNG) and hydrogen. The implementation of these alternatives can help take care to the high demand of environment friendly vehicles. These natural gas fuels when blended with diesel are expected to decrease emissions along-with reduction of the petroleum fuel consumption. Diesel mixed with hydrogen and methane in different concentrations enhances the performance and efficiency of vehicles. A numerical study were conducted to observe the impact of diesel mixed with hydrogen and methane (dual or tri-fuel) in the combustion process. Intake temperature was increased in between 303 K to 338 K. The simulation of the combustion process used ANSYS Fluent software based on a Yanmar L100AED single-cylinder engine parameter. The simulation conducted with engine speed of 1500 rpm, compression ratio (CR) = 19.3, and λ = 1.2 at different intake temperatures. The results compared the combustion process between a baseline fuel (100% diesel) and diesel-hydrogen-methane tri-fuel. The study found that the optimum intake temperature to enhance performance relies on a concentration of gaseous mixed with diesel. The highest performance and efficiency were obtained at 318 K intake temperature using tri-fuel of 60D-28H-12CH4 . From the in-cylinder pressure and temperature, results show increased in performance when the amount of hydrogen increased at the intake temperature. In conclusion, increasing the intake temperature and the use of tri-fuel in a direct ignition engine significantly improved the performance and efficiency of the engine.